"ONE STEP AHEAD AND TWO STEPS BACK": MEETING SPECIAL EDUCATION AND INCLUSIVE CHALLENGES IN THE CONTEXT OF POVERTY (CASE STUDY IN THE CONTEXT OF REPUBLIC OF MOLDOVA). (August 2016) - Kalinnikova Magnusson, Liya
Abstract : The research experience is based on outputs from the international project «Human resources in poverty and disability: family perspective (Moldova and Ukraine): 348‐2011‐7346 [2012‐2014]», funded by the Vetenskapsrådet, Sweden. During the last 20 years, Moldavian and Ukrainian societies have been developing inclusive infrastructures, being under complicated transformative changes. There are two main tendencies of the current situation for children with disabilities. The first one is that the inherited system of internat special schools is rapidly changing its functions, expanding, due to work with children from marginal families. In this case, economic polarisation forms a specific family strategy to protect their children from family economic problems, 'intentionally putting' their children in these special school internats. The second strategy is directed towards deinstitutionalisation of the system of special school internats, the development of inclusive infrastructure and involvement the non‐profit organisations, etc. This paper discusses these tendencies, through a case study approach.